Playing devil’s advocate - Etienne Achille (Francosphères)
While Pierre Nora’s seminal collection Les Lieux de mémoire (1984–1992) has been continuously praised for the elaboration of a groundbreaking paradigm, it has also been the object of a significant amount of criticism due notably to the ‘nothing short of fantastic’ absence of references to the French colonial past. However, when sifting through the seven volumes’ 5,000+ pages, it becomes obvious that if the colonial has not been granted its due place, it is not at all absent, with at least 38 of the 132 entries broaching the topic. The objective of this article will be first to highlight and reflect upon these textual and visual colonial traces, and then question why an influential study that has elicited so much interest and commentary for almost thirty years continues to be presented as a work deprived of any reference to colonial heritage apart from Charles-Robert Ageron’s entry on the Paris 1931 exhibition. Ultimately, it is the attitude of scholars towards the roman national that this article wishes to interrogate, while proposing to rethink the ways in which a wider postcolonial sensibility may be reinforced in the challenging context of contemporary France.